Studying the Effect of Initial Damage on Failure Probability of One Story Steel Buildings - F. Nateghi; N. Parsaeifard (Iranica Journal of Energy and Environment, 2013)
Progressive collapse is a kind of failure in which the collapse of one or several load bearing elementsis ended in partial or total collapse of structures. If earthquakes induce progressive collapse, seismic and gravityloads cause initial failure propagating to other parts of structures. Therefore, seismic progressive collapse canoccur in structures regardless the number of stories. In this paper the behavior of a one story steel building isstudied to investigate the effect of initial damaged column position on the seismic progressive collapse. In thisregard the critical position of damaged column has been identified first and then, the effect of damaged columnis studied. Accordingly, nonlinear dynamic analysis has been used to obtain the fragility curves of the structureand investigate its failure probability. A damage index has also been used to validate the results. Based on theresults obtained in this research, the initial failure of a middle column can increase the failure probability ofstructures during earthquakes. Besides, among the evaluated design parameters, the failure probability ischanged significantly in the columns in accordance with their axial loads.